Limits of Criminalization of False News AsCriminal Acts in Elections - Sukadana, Dewa Ayu Putri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The serious danger of election hoaxes is when the hoax is conveyed to the public who are very apathetic or in people who do not trust the current government, and distributed massively ahead of voting day. It is at this stage that hoaxes can intervene free choice of voters who have greater autonomy.